Changes in land use conflict and zoning optimization in rapidly developing mountainous cities: a case study of Guiyang, China - Han, Huiqing; Zhang, Kexin; Ma, Geng (Journal of Environmental Engineering and Landscape Management, 2025)
Mountainous cities, influenced by complex human activities and terrain, face severe land use conflict issues. However, the spatiotemporal characteristics of land use conflict changes and the scientific questions regarding their management in rapidly developing mountainous cities remain unresolved. Therefore, Guiyang, a typical mountainous city in China, was chosen as the study area. With the support of ArcGIS technology, this research analyzed land use conflict changes and conducted zoning optimization. The study reveals a rapid intensification of land use conflicts, with high conflict areas increasing by 369%, while moderate, general, and low conflict areas declined. The conflict between production and living spaces is the predominant one, expanding by 385%. Additionally, high conflict areas between production and ecological spaces rose by 760%. Integrating land suitability, conflict, and functional differences in zoning optimization enhances core functions, mitigates conflicts, and guides land use management. The results are valuable for optimizing land use patterns and promoting healthy urban development in mountainous cities.